Misbehaving High‐Energy Electrons: Evidence in Support of Ubiquitous Wave‐Particle Interactions on Dayside Martian Closed Crustal Magnetic Fields. Issue 21 (7th November 2019) - Shane, Alexander; Liemohn, Michael; Florie, Corinne; Xu, Shaosui
Abstract: Multiple studies have reported either isotropic or trapped pitch angle distributions of high‐energy (>100 eV) electrons on closed crustal field lines on the dayside of Mars. These pitch angle distributions are not to be expected from collisional scattering and conservation of adiabatic invariants alone. We use 2 years of data from the Mars Atmosphere and Volatile EvolutioN mission to analyze the pitch angle distributions of superthermal electrons on dayside‐closed crustal magnetic fields and compare to results from an electron transport model. Low‐energy electrons (10–60 eV) have pitch angle distributions in agreement with modeling results, while high‐energy electrons (100–500 eV) do not. High‐energy electrons have a flux peak at perpendicular pitch angles which suggests there is a ubiquitous energization process occurring on crustal fields. Wave‐particle interactions seem to be the most likely candidate. Trapping of high‐energy electrons may impact the nightside ionosphere dynamics. Plain Language Summary: Superthermal electrons are electrons with energies between 1 and 1, 000 eV and can be produced from ionizing a neutral atmospheric molecule (photoelectron). These electrons are efficient at shifting energy around in space environments due to their high speeds and their ability to interact with the more ubiquitous lower energy (thermal) plasma. Past studies have investigated the distribution of photoelectrons on the crustal magnetic fields of Mars, and they do not always agree with past modeling results and a basic understanding of electron transport. In this study, we use data from the Mars Atmosphere and Volatile EvolutioN mission in order to understand the distribution of these electrons throughout the Mars space environment, previously impossible due to spacecraft orbits. We find that the lower energy electrons (10–60 eV) behave as expected but the higher‐energy electrons (100–500 eV) do not. We find that the type of distribution statistically seen by Mars Atmosphere and Volatile EvolutioN for these high‐energy electrons suggests that a ubiquitous energization process is occurring on the dayside crustal magnetic fields of Mars. We consider multiple physical processes capable of producing such observed distributions and conclude that wave‐particle interactions are the most likely candidate. Key Points: Low‐energy photoelectrons on the Martian dayside have pitch angle distributions consistent with conservation of adiabatic invariants High‐energy electrons on the Martian dayside have a flux peak at perpendicular pitch angles, indicating a ubiquitous energization process Wave‐particle interactions are the most likely candidate to produce such distributions for high‐energy electrons